PENDIDIKAN AGAMA ISLAM DALAM RANGKA PENANGGULANGAN RADIKALISASI - Arum Rohmiyati; Irma Deni; Eko Sawandi; Milana Abdillah Subarkah (STAI Pelabuhan Ratu, 2023)
The phenomenon of religious radicalism has become a global threat of the 21st century, the phenomenon is the result of Islam as an alleged religion and is often associated with terrorist religions. Educational institutions are often